Asesmen Daur Hidup (ADH) Plastik - Hendartini Hendartini (Jurnal Kimia dan Kemasan, 1996)
The movement to wards adopting the concepts of sustainable development is causing industries to minimize the environmental impact of their activities and the products that they produce. One of the everyday goods that rapidly grown is plastics. Concern to that concept, plastic industries have invested a field of research known as Life Cycle Assessment - ascientific technique designed to provide an environmental profile of a product from cradle to grave. LCA has enabled us to discover much about the relative effects of differentsubstances and process. LCA as a component on Environmental Management System has been studied to become series ofISO 14000 that is ISO 14041 - 14044.